2017
DOI: 10.1093/gji/ggx159
|View full text |Cite
|
Sign up to set email alerts
|

Fracture connectivity can reduce the velocity anisotropy of seismic waves

Abstract: The degree of connectivity of fracture networks is a key parameter that controls the hydraulic properties of fractured rock formations. The current understanding is that this parameter does not alter the effective elastic properties of the probed medium and, hence, cannot be inferred from seismic data. However, this reasoning is based on static elasticity, which neglects dynamic effects related to wave-induced fluid pressure diffusion (FPD). Using a numerical upscaling procedure based on the theory of quasi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 16 publications
5
64
0
Order By: Relevance
“…Consequently, there is a given frequency for which, V P (45 ∘ ) = V P (0 ∘ ) = V P (90 ∘ ) and the P wave phase velocity is virtually isotropic. These results are in agreement with the findings of Rubino et al () who showed that the level of phase velocity anisotropy produced by the presence of fractures is strongly affected by the degree of hydraulic connectivity of the fracture network. Moreover, they found that, in the case of low‐permeability formations and fully connected fractures, the regime where V P (45 ∘ ) ∼ V P (0 ∘ ) ∼ V P (90 ∘ ) prevails in the seismic frequency band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is a given frequency for which, V P (45 ∘ ) = V P (0 ∘ ) = V P (90 ∘ ) and the P wave phase velocity is virtually isotropic. These results are in agreement with the findings of Rubino et al () who showed that the level of phase velocity anisotropy produced by the presence of fractures is strongly affected by the degree of hydraulic connectivity of the fracture network. Moreover, they found that, in the case of low‐permeability formations and fully connected fractures, the regime where V P (45 ∘ ) ∼ V P (0 ∘ ) ∼ V P (90 ∘ ) prevails in the seismic frequency band.…”
Section: Resultsmentioning
confidence: 99%
“…The maximal S wave attenuation occurs at an angle of incidence of ∼45°, and it is particularly strong in the FF‐WIFF regime. As pointed out by Rubino et al (), this is related to the fact that the induced pressures are positive and negative in the horizontal and vertical fractures, respectively, and hence, the fluid pressure gradient between connected fractures is particularly large.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of papers, Rubino et al (2013Rubino et al ( , 2014Rubino et al ( , and 2017 found that besides FB-WIFF, WIFF also occurs within connected mesoscopic fractures (FF-WIFF), which can have a significant influence on the dispersion, attenuation, and anisotropy of seismic waves. Since this fluid flow critically depends on the connectivity degree of the probed fracture network, these results suggest the possibility to detect fracture connectivity and, hence, to quantify the effective permeability of fractured formations using seismic data.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the FB-WIFF, in the recent studies of Rubino et al (2013Rubino et al ( , 2014Rubino et al ( , and 2017, it is found that the WIFF also occurs within the connected fractures (FF-WIFF). It is shown that FF-WIFF can also result in significant seismic dispersion and attenuation.…”
Section: Introductionmentioning
confidence: 97%